Formulation and Evaluation of Immediate Release Tablet of Carvedilol using Liquisolid Compacts Technique for Solubility Enhancement - Jamakandi, Dr. Vilas G. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study was to formulate and evaluate liquisolid compact system of carvedilol to give increased dissolution rate of drug by utilizing PEG400 as the non-volatile liquid vehicle. Materials and Methods: The liquisolid tablets formulated with PEG400 at different concentrations. The suitable analytical method based on UV-visible spectrophotometer was developed for carvedilol. Results and Discussion: The results of differential scanning calorimeter and Fourier transform infrared analysis confirmed that the excipients are compatible with the drug. The liquisolid tablets formulated with PEG400 at drug concentration 20% w/w is the best formulations among the other 10 batches of liquisolid tablet prepared, in terms of superior dissolution profile. LSC3 with R value 15 gave the maximum drug release. Short term accelerated stability study of optimized formulation (LSC3) of carvedilol was carried out at 40°C ± 2°C and at 75% ± 5% RH for 1 month. Conclusion: Immediate release tablet of carvedilol using liquisolid compacts technique was prepared and evaluated for the compatibility studies. No significant change or variation was observed in any parameters throughout the study.